SIMULASI PEMBEBANAN GIGI PERONTOK THRESHER BUAH PINANG (Areca catechu) MENGGUNAKAN METODE ELEMEN TAK HINGGA - Sriyono Sriyono; Dewi Sartika T; Aries Karyadi; Agustami Sitorus; Ramayanty Bulan (AGROINTEK, 2021)
The design approach of a machine is a critical factor in deciding its performance. On the one, a really stronger material may be used in these machine components, but the associated costs would be higher due to overdesign (and vice versa). As a result, before beginning the production process, it is essential to study the critical points of machine components thoroughly. It would be the same if we were to design a betel nut thresher unit. The bow tooth is a crucial part of the areca thresher's design. The teeth are the parts that interact directly with the betel nut to release it from the betel nut bunch. Therefore, in this paper conducted a simulation using the finite element method (FEM) to determine the appropriate shape of the thresher tooth threshing machine for betel nuts. Three shapes of teeth that were tested in this simulation are teeth of round (type-A), rectangular (type-B), and hexagonal (type-C) teeth. The type of material that will be used to become tooth decay is ductile iron. The shape and type of this material are chosen based on the materials commonly used in Indonesia. The parameters used in the simulation include strain, stress, and displacement. The results showed that the rectangular (type-B) bow tooth could spread the shedding load better than other bow tooth types for betel nut thresher unit.